2015
DOI: 10.1021/cm504448u
|View full text |Cite
|
Sign up to set email alerts
|

Ultraporous Mesostructured Silica Nanoparticles

Abstract: M esoporous silica materials find use in many applications such as catalysis, separations, drug delivery, and gas adsorption wherein a large pore volume is desirable. 1−4 High pore volumes can be achieved by swelling traditional surfactant templates, 5−8 by employing larger templates such as block copolymers 9,10 or sacrificial nanoparticles, 11,12 or through interface-directed syntheses. 13−20 For example, Stucky and coworkers demonstrated structural control over silica materials at two size scales by utiliz… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
66
0
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 56 publications
(68 citation statements)
references
References 34 publications
1
66
0
1
Order By: Relevance
“…In our previous study with bare UMNs, scanning electron microscopy analysis revealed a spherical 3D–structure with raspberry-like surface textures. 39 …”
Section: Resultsmentioning
confidence: 99%
“…In our previous study with bare UMNs, scanning electron microscopy analysis revealed a spherical 3D–structure with raspberry-like surface textures. 39 …”
Section: Resultsmentioning
confidence: 99%
“…From the TEM observation, the sizes of radial pores are smaller than that observed in the SEM images. Moreover, it is hard to unambiguously determine whether A‐HDMSN have a hollow cavity, or the shape of radial pores in the silica walls …”
Section: Resultsmentioning
confidence: 99%
“…Moreover, it is hard to unambiguously determine whether A-HDMSN have a hollow cavity, or the shape of radial pores in the silica walls. [ 35 ] Electron tomography (ET) [ 27,30,36,37 ] was applied to further explore the detailed structure of A-HDMSN. An ET slice cutting across the center of one A-HDMSN particle clearly shows a hollow central core with ≈170 nm in diameter (Figure 1 d).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Among bioinorganic nanomaterials [5], mesoporous silica and organosilica nanoparticles (NPs) are promising hybrid nanomaterials for biomedical applications [6,7]. Silica particles have indeed many unique benefits such as tunable dissolution rates from under a day to months [1], high surface areas and pore volumes (e.g., 1000-1500 m 2 ·g −1 ; 1.0-4.5 cm 3 ·g −1 ) [8,9], and can be produced in kilogram quantities while maintaining a high control of particle monodispersity [10]. Silica can be hybridized using organic and inorganic doping strategies to mediate biodegradability through pH [11,12], enzymatic [12][13][14], redox [3,[15][16][17][18], and biochelation [19][20][21][22] mechanisms [1,2].…”
Section: Introductionmentioning
confidence: 99%